The Effect of learning methods and arm muscle strength on handstand learning outcomes - sulistiadinata, Heru; Nugraha, Angga (Journal of Physical and Outdoor Education, 2023)
The background of this research is that regular physical activity is inseparable from the improvement of students' psychomotor, cognitive, and affective. Handstand skills are fundamental to a floor gymnast. The purpose of this study was to see the effect of the learning method (partial and whole) and arm muscle strength on the learning outcomes of floor exercise handstands. This study used a 2 x 2 by level group design. This research was conducted on students of SMAN 1 Cimalaka. The results of the study with , show that there is an influence of learning methods and arm muscle strength together on the learning outcomes of floor exercise handstands.